Environmental management in Tasmania: better off dead? - Paull, J (Springer, 2011)
Tasmania is Australia’s island state. It has been isolated from the Australian mainland for millennia, and its biota exhibit a high degree of endemism. Tasmania was the final refuge for the world’s largest marsupial carnivore, the thylacine. After tens of millennia of co-existence with the Tasmanian aborigines, the thylacine was successfully exterminated. This was the culmination of a century-long bounty program starting in 1830. The last thylacine died in captivity in 1936. From 1952 Tasmania has pioneered the widespread use of the poison sodium fluoroacetate (1080), a contaminant of which is a tumorigen, against its native marsupials. With the thylacine exterminated, the Tasmanian devil is currently the world’s largest marsupial carnivore. Like the thylacine before it, Tasmania is the last refuge of the devil. The future of this endemic species is now uncertain due to the outbreak amongst many of these animals of serious tumours, dubbed Devil Facial Tumour Disease (DFTD). The European fox could theoretically step into the biological niche of top-level predator vacated by the thylacine. The Tasmanian Government has embarked on an expensive and extensive poison-baiting of the island targeting a claimed fox infestation, an infestation lacking hard evidence and one that is treated with great skepticism by many. Are these ‘better-off-dead’ environmental management approaches an unfortunate relic of the past, or do they really point the path to the future?